Ceramic splitting knife material and preparation method thereof

By using a combination formula of matrix ceramic, multi-alloy oxide and nanomaterials in ceramic splitting materials, combined with ball milling and sintering processes, the problem of insufficient hardness and bending strength of ceramic splitting materials is solved, and efficient preparation and long life are achieved and ceramic splitting knife materials with high mechanical properties.

CN118530008BActive Publication Date: 2024-12-13苏州芯合半导体材料有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410977755.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2024-12-13
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

The existing ceramic splitting knife materials have insufficient hardness, unstable grain structure, low bending strength, and need to be improved, resulting in low grinding efficiency and short service life.

Method used

Using a combination formula of matrix ceramics, multi-alloy oxides, binders and nanomaterials, ceramic splitting materials are prepared through ball milling, drying, sieving, glue discharge and sintering, etc., to improve its hardness and grain structure stability. and bending strength.

Benefits of technology

The prepared ceramic splitting knife material has high hardness, stable grain structure, good fracture toughness and bending strength, long service life, simple process and convenient operation and control, and is suitable for continuous and large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118530008B_ABST
    Figure CN118530008B_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic splitting knife material and a preparation method thereof, which relates to the technical field of ceramic materials, and comprises the following components by weight: 60-80 parts of matrix ceramic, 15-25 parts of multi-element alloy oxide, 5-8 parts of binder, 5-10 parts of other nanomaterials, 2-4 parts of dispersant, and 0.8-1.2 parts of stearic acid; the multi-element alloy oxide is Mn-Mo-V-Hf-Cu-Cr-Ta-Al-B-O; the binder comprises the following raw materials: cellulose nanocrystals, sodium silicate, 2,4,6-trivinyl cycloboroxine, N-trimethylol methacrylamide, 2,4-diamino-6-diallylamino-1,3,5-triazine, vinyl trimethoxysilane, and initiator. The ceramic splitting knife material has sufficient hardness, stable grain structure, good fracture toughness and flexural strength, high density, and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a ceramic splitting knife material and a preparation method thereof. Background Art

[0002] In the semiconductor packaging industry, most low-cost mid-range packaging and memory chip stacking and other packaging processes are inseparable from ceramic splitters. Ceramic splitters are an axisymmetric ceramic tool with a vertical hole. Because of their high hardness, high wear resistance, high temperature resistance, chemical corrosion resistance, high surface finish and high dimensional accuracy, they play an irreplaceable role in the field of semiconductor wire bonding welding. They are widely used in semiconductor IC packaging and LED packaging, and are one of the core materials in the chip packaging bonding process.

[0003] The existing preparation process of ceramic splitters is to mix ceramic powder and binder to prepare feed, injection mold the feed into a splitter green body, sinter the splitter green body to make it dense, and finally grind the densified splitter to obtain a finished splitter. However, such a preparation method makes the grinding process difficult, the grinding efficiency of the splitter is low, and the grinding wheel is seriously damaged due to the high hardness and strength of the densified splitter. On the other hand, the ceramic splitter materials on the market still have more or less technical defects such as insufficient hardness, unstable grain structure, fracture toughness and bending strength need to be further improved, and density needs to be further improved.

[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN116199501B discloses an alumina ceramic splitter based on photocuring and a manufacturing method thereof, the method comprising the steps of: S1, preparing a ceramic slurry with a solid content of 53-58 vol%, the ceramic slurry composition comprising a modified ceramic powder, a high refractive index photosensitive resin monomer, a photoinitiator and a plasticizer; S2, layering the 3D model of the ceramic splitter to be printed through a three-dimensional software, determining the shape of each layer to be exposed and polymerized, and generating a printing control program; S3, performing photocuring printing to obtain a ceramic blank; S4, cleaning the ceramic blank; S5, vacuum-air debinding and sintering the cleaned ceramic blank to obtain a finished ceramic splitter part. However, the ceramic splitter has large grains, low bending strength, is not wear-resistant, and has a short life.

[0005] It can be seen that the development of a ceramic splitting knife material and its preparation method with sufficient hardness, stable grain structure, good fracture toughness and bending strength, high density and long service life meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the chip packaging and bonding field. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a ceramic splitting knife material having sufficient hardness, stable grain structure, good fracture toughness and bending strength, high density and long service life and a preparation method thereof.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is: a ceramic splitter material, comprising the following components in parts by weight: 60-80 parts of matrix ceramic, 15-25 parts of multi-element alloy oxide, 5-8 parts of binder, 5-10 parts of other nanomaterials, 2-4 parts of dispersant, and 0.8-1.2 parts of stearic acid; the multi-element alloy oxide is Mn-Mo-V-Hf-Cu-Cr-Ta-Al-BO; the binder comprises the following raw materials in parts by weight: 6-8 parts of cellulose nanocrystals, 3-5 parts of sodium silicate, 1-3 parts of 2,4,6-trivinyl cycloboroxine, 1-3 parts of N-trihydroxymethyl methacrylamide, 1-2 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 1-3 parts of vinyl trimethoxysilane, and 0.04-0.1 parts of initiator.

[0008] Preferably, the matrix ceramic is a mixture of alumina powder, rare earth oxide powder and zirconium oxide powder in a mass ratio of (50-70):(8-12):(10-20).

[0009] Preferably, the particle size of the matrix ceramic is 1000-1500 mesh; the rare earth oxide powder is a mixture of scandium oxide powder, yttrium oxide powder and cerium oxide powder in a mass ratio of 0.2:(0.8-1.2):1.

[0010] Preferably, the preparation method of the multi-element alloy oxide comprises the following steps: adding an aluminum source, a manganese source, a molybdenum source, a vanadium source, a hafnium source, a copper source, a chromium source, a tantalum source, a boron source and citric acid to water, mixing them evenly, spray drying to obtain a precursor, then calcining the precursor, taking it out and grinding it, passing it through a 300-500 mesh sieve to obtain the multi-element alloy oxide.

[0011] Preferably, the aluminum source is at least one of aluminum nitrate and aluminum chloride; the manganese source is at least one of manganese nitrate and manganese chloride; the molybdenum source is at least one of molybdenum nitrate and molybdenum chloride; the vanadium source is vanadium nitrate; the hafnium source is hafnium tetranitrate; the copper salt is at least one of copper nitrate and copper sulfate; the chromium source is chromium nitrate; and the boron source is sodium borate.

[0012] Preferably, the mass ratio of the aluminum source, manganese source, molybdenum source, vanadium source, hafnium source, copper source, chromium source, tantalum source, boron source, citric acid and water is 1:(0.1-0.2):0.05:(0.05-0.08):(0.01-0.03):(0.08-0.15):(0.15-0.25):0.01:0.001:0.5:(8-12).

[0013] Preferably, the calcination is carried out in two steps, the first step is a constant temperature pre-calcination at 450-550° C. in a muffle furnace for 1-3 hours, and the second step is a calcination at 800-900° C. in a muffle furnace for 6-9 hours.

[0014] Preferably, the other nanomaterials are a mixture of nano zirconium boride, nano niobium boride, nano titanium nitride and nano silicon nitride in a mass ratio of 1:(0.8-1.2):(1-2):0.8.

[0015] Preferably, the particle size of the other nanomaterials is 10-80 nm.

[0016] Preferably, the dispersant is at least one of soybean lecithin, polyethylene glycol 200 and polyethylene glycol 400.

[0017] Preferably, the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Nanosyn Technology Co., Ltd.

[0018] Preferably, the initiator is azobisisobutyronitrile.

[0019] Another object of the present invention is to provide a method for preparing the ceramic splitting knife material, comprising the following steps:

[0020] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0021] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0022] Step S3: sintering the green body to obtain a ceramic splitting knife material.

[0023] Preferably, the drying in step S2 is carried out under vacuum, the drying time is 18-22 hours, and the drying temperature is 78-90°C.

[0024] Preferably, the sieving in step S2 is through a 100-300 mesh sieve; the debinding is performed in a vacuum environment, the debinding temperature is 450-520° C., and the debinding time is 3-5 hours.

[0025] Preferably, the sintering conditions in step S3 are: heating rate 2-6°C / min, sintering temperature 1450-1650°C, and holding time 5-10h.

[0026] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0027] (1) The preparation method of the ceramic splitting knife material disclosed in the present invention has simple process, convenient operation and control, high preparation efficiency and finished product qualification rate, low energy consumption, low dependence on equipment, is suitable for continuous large-scale production, and has high promotion and application value.

[0028] (2) The ceramic splitting knife material disclosed in the present invention comprises the following components in parts by weight: 60-80 parts of base ceramic, 15-25 parts of multi-element alloy oxide, 5-8 parts of binder, 5-10 parts of other nanomaterials, 2-4 parts of dispersant, and 0.8-1.2 parts of stearic acid. Through the mutual cooperation between the components, the prepared ceramic splitting knife material has sufficient hardness, stable grain structure, good fracture toughness and bending strength, high density, and long service life.

[0029] (3) The ceramic splitter material disclosed in the present invention, the other nano materials are a mixture of nano zirconium boride, nano niobium boride, nano titanium nitride, and nano silicon nitride in a mass ratio of 1: (0.8-1.2): (1-2): 0.8; the multi-element alloy oxide is Mn-Mo-V-Hf-Cu-Cr-Ta-Al-BO; the binder comprises the following raw materials in parts by weight: 6-8 parts of cellulose nanocrystals, 3-5 parts of sodium silicate, 1-3 parts of 2,4,6-trivinyl cycloboroxane, 1-3 parts of N-trimethylolmethyl acrylamide, 1-2 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 1-3 parts of vinyl trimethoxysilane, and 0.04-0.1 parts of initiator. Through the reasonable selection of the above raw materials and formula, the prepared splitter material has a dense crystal phase, uniform structure, greater material hardness, good bonding quality, high reliability of welding points, and long service life.

[0030] (4) The ceramic splitting knife material disclosed in the present invention, through the reasonable selection of various process parameters during the preparation process, makes the prepared splitting knife material have more uniform and refined structure, higher hardness, more stable grain structure, better fracture toughness and bending strength, higher density and longer service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a microstructure diagram of the ceramic splitting knife material according to Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0033] Embodiment 1, a ceramic splitting knife material, comprising the following components in parts by weight: 60 parts of base ceramic, 15 parts of multi-element alloy oxide, 5 parts of binder, 5 parts of other nanomaterials, 2 parts of dispersant, and 0.8 parts of stearic acid; the multi-element alloy oxide is Mn-Mo-V-Hf-Cu-Cr-Ta-Al-BO; the binder comprises the following raw materials in parts by weight: 6 parts of cellulose nanocrystals, 3 parts of sodium silicate, 1 part of 2,4,6-trivinyl cycloboroxine, 1 part of N-trihydroxymethyl methacrylamide, 1 part of 2,4-diamino-6-diallylamino-1,3,5-triazine, 1 part of vinyl trimethoxysilane, and 0.04 parts of initiator.

[0034] The matrix ceramic is a mixture of aluminum oxide powder, rare earth oxide powder and zirconium oxide powder in a mass ratio of 50:8:10; the rare earth oxide powder is a mixture of scandium oxide powder, yttrium oxide powder and cerium oxide powder in a mass ratio of 0.2:0.8:1; the particle size of the matrix ceramic is 1000 mesh.

[0035] The preparation method of the multi-element alloy oxide comprises the following steps: adding an aluminum source, a manganese source, a molybdenum source, a vanadium source, a hafnium source, a copper source, a chromium source, a tantalum source, a boron source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out, grinding it, and passing it through a 300-mesh sieve to obtain the multi-element alloy oxide; the aluminum source is aluminum nitrate; the manganese source is manganese nitrate; the molybdenum source is molybdenum nitrate; the vanadium source is vanadium nitrate; the hafnium source is hafnium tetranitrate; the copper salt is copper nitrate; the chromium source is chromium nitrate; the boron source is sodium borate; and the mass ratio of the aluminum source, manganese source, molybdenum source, vanadium source, hafnium source, copper source, chromium source, tantalum source, boron source, citric acid and water is 1:0.1:0.05:0.05:0.01:0.08:0.15:0.01:0.001:0.5:8.

[0036] The calcination is carried out in two steps, the first step is to pre-calculate at a constant temperature of 450° C. for 1 hour in a muffle furnace, and the second step is to calcine at 800° C. for 6 hours in a muffle furnace; the other nanomaterials are a mixture of nano-zirconium boride, nano-niobium boride, nano-titanium nitride, and nano-silicon nitride in a mass ratio of 1:0.8:1:0.8; the particle size of the other nanomaterials is 10 nm; the dispersant is soybean lecithin; the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Naxun Technology Co., Ltd.; the initiator is azobisisobutyronitrile.

[0037] A method for preparing the ceramic splitting knife material comprises the following steps:

[0038] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0039] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0040] Step S3: sintering the green body to obtain a ceramic splitting knife material.

[0041] The drying in step S2 is carried out under vacuum, the drying time is 18 hours, and the drying temperature is 78°C; the screening in step S2 is through a 100-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 450°C, and the debinding time is 3 hours.

[0042] The sintering conditions in step S3 are: heating rate 2°C / min, sintering temperature 1450°C, and holding time 5h.

[0043] from Figure 1 It can be seen that the ceramic splitting knife material has a dense crystal phase and a uniform structure.

[0044] Embodiment 2, a ceramic splitting knife material, comprising the following components in parts by weight: 65 parts of base ceramic, 17 parts of multi-element alloy oxide, 6 parts of binder, 6 parts of other nanomaterials, 2.5 parts of dispersant, and 0.9 parts of stearic acid; the multi-element alloy oxide is Mn-Mo-V-Hf-Cu-Cr-Ta-Al-BO; the binder comprises the following raw materials in parts by weight: 6.5 parts of cellulose nanocrystals, 3.5 parts of sodium silicate, 1.5 parts of 2,4,6-trivinyl cycloboroxine, 1.5 parts of N-trihydroxymethyl methacrylamide, 1.2 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 1.5 parts of vinyl trimethoxysilane, and 0.06 parts of initiator.

[0045] The matrix ceramic is a mixture of aluminum oxide powder, rare earth oxide powder and zirconium oxide powder in a mass ratio of 55:9:12; the rare earth oxide powder is a mixture of scandium oxide powder, yttrium oxide powder and cerium oxide powder in a mass ratio of 0.2:0.9:1; the particle size of the matrix ceramic is 1200 mesh.

[0046] The preparation method of the multi-element alloy oxide comprises the following steps: adding an aluminum source, a manganese source, a molybdenum source, a vanadium source, a hafnium source, a copper source, a chromium source, a tantalum source, a boron source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out, grinding it, and passing it through a 350-mesh sieve to obtain the multi-element alloy oxide; the aluminum source is aluminum chloride; the manganese source is manganese chloride; the molybdenum source is molybdenum chloride; the vanadium source is vanadium nitrate; the hafnium source is hafnium tetranitrate; the copper salt is Copper sulfate; the chromium source is chromium nitrate; the boron source is sodium borate; the mass ratio of the aluminum source, manganese source, molybdenum source, vanadium source, hafnium source, copper source, chromium source, tantalum source, boron source, citric acid and water is 1:0.13:0.05:0.06:0.015:0.1:0.17:0.01:0.001:0.5:9; the roasting is carried out in two steps, the first step is to pre-fire at a constant temperature of 470°C in a muffle furnace for 1.5 hours, and the second step is to roast at 830°C in a muffle furnace for 7 hours.

[0047] The other nanomaterials are a mixture of nano-zirconium boride, nano-niobium boride, nano-titanium nitride and nano-silicon nitride in a mass ratio of 1:1:1.5:0.8; the particle size of the other nanomaterials is 30nm; the dispersant is polyethylene glycol 200; the cellulose nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.; the initiator is azobisisobutyronitrile.

[0048] A method for preparing the ceramic splitting knife material comprises the following steps:

[0049] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0050] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0051] Step S3: sintering the green body to obtain a ceramic splitting knife material.

[0052] The drying in step S2 is carried out under vacuum, the drying time is 19 hours, and the drying temperature is 82°C; the screening in step S2 is through a 150-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 470°C, and the debinding time is 3.5 hours.

[0053] The sintering conditions in step S3 are: heating rate 3°C / min, sintering temperature 1500°C, and holding time 6h.

[0054] Embodiment 3, a ceramic splitting knife material, comprising the following components in parts by weight: 70 parts of base ceramic, 20 parts of multi-element alloy oxide, 6.5 parts of binder, 7.5 parts of other nanomaterials, 3 parts of dispersant, and 1 part of stearic acid; the multi-element alloy oxide is Mn-Mo-V-Hf-Cu-Cr-Ta-Al-BO; the binder comprises the following raw materials in parts by weight: 7 parts of cellulose nanocrystals, 4 parts of sodium silicate, 2 parts of 2,4,6-trivinylcycloboroxine, 2 parts of N-trihydroxymethylmethylacrylamide, 1.5 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 2 parts of vinyltrimethoxysilane, and 0.07 parts of initiator.

[0055] The matrix ceramic is a mixture of aluminum oxide powder, rare earth oxide powder and zirconium oxide powder in a mass ratio of 60:10:15; the rare earth oxide powder is a mixture of scandium oxide powder, yttrium oxide powder and cerium oxide powder in a mass ratio of 0.2:1:1; the particle size of the matrix ceramic is 1300 mesh.

[0056] The preparation method of the multi-element alloy oxide comprises the following steps: adding an aluminum source, a manganese source, a molybdenum source, a vanadium source, a hafnium source, a copper source, a chromium source, a tantalum source, a boron source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out, grinding it, and passing it through a 400-mesh sieve to obtain the multi-element alloy oxide; the aluminum source is aluminum nitrate; the manganese source is manganese nitrate; the molybdenum source is molybdenum nitrate; the vanadium source is vanadium nitrate; the hafnium source is hafnium tetranitrate; the copper salt is nitrate acid copper; the chromium source is chromium nitrate; the boron source is sodium borate; the mass ratio of the aluminum source, manganese source, molybdenum source, vanadium source, hafnium source, copper source, chromium source, tantalum source, boron source, citric acid and water is 1:0.15:0.05:0.065:0.02:0.11:0.2:0.01:0.001:0.5:10; the calcination is carried out in two steps, the first step is to pre-calculate at a constant temperature of 500°C in a muffle furnace for 2h, and the second step is to calcine at 850°C in a muffle furnace for 7.5h.

[0057] The other nanomaterials are a mixture of nano-zirconium boride, nano-niobium boride, nano-titanium nitride and nano-silicon nitride in a mass ratio of 1:1:1.5:0.8; the particle size of the other nanomaterials is 50nm; the dispersant is polyethylene glycol 400; the cellulose nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.; the initiator is azobisisobutyronitrile.

[0058] A method for preparing the ceramic splitting knife material comprises the following steps:

[0059] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0060] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0061] Step S3: sintering the green body to obtain a ceramic splitting knife material.

[0062] The drying in step S2 is carried out under vacuum, the drying time is 20 hours, and the drying temperature is 84°C; the screening in step S2 is through a 200-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 490°C, and the debinding time is 4 hours.

[0063] The sintering conditions in step S3 are: heating rate 4°C / min, sintering temperature 1550°C, and holding time 8h.

[0064] Embodiment 4, a ceramic splitting knife material, comprising the following components in parts by weight: 75 parts of base ceramic, 23 parts of multi-element alloy oxide, 7.5 parts of binder, 9 parts of other nanomaterials, 3.5 parts of dispersant, and 1.1 parts of stearic acid; the multi-element alloy oxide is Mn-Mo-V-Hf-Cu-Cr-Ta-Al-BO; the binder comprises the following raw materials in parts by weight: 7.5 parts of cellulose nanocrystals, 4.5 parts of sodium silicate, 2.5 parts of 2,4,6-trivinylcycloboroxine, 2.5 parts of N-trihydroxymethylmethylacrylamide, 1.8 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 2.5 parts of vinyltrimethoxysilane, and 0.09 parts of initiator.

[0065] The matrix ceramic is a mixture of aluminum oxide powder, rare earth oxide powder and zirconium oxide powder in a mass ratio of 65:11:18; the rare earth oxide powder is a mixture of scandium oxide powder, yttrium oxide powder and cerium oxide powder in a mass ratio of 0.2:1.1:1; the particle size of the matrix ceramic is 1400 mesh.

[0066] The preparation method of the multi-element alloy oxide comprises the following steps: adding an aluminum source, a manganese source, a molybdenum source, a vanadium source, a hafnium source, a copper source, a chromium source, a tantalum source, a boron source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out, grinding it, and passing it through a 450-mesh sieve to obtain the multi-element alloy oxide; the aluminum source is a mixture of aluminum nitrate and aluminum chloride in a mass ratio of 3:5; the manganese source is a mixture of manganese nitrate and manganese chloride in a mass ratio of 1:3; the molybdenum source is a mixture of molybdenum nitrate and molybdenum chloride in a mass ratio of 1:2; the vanadium source is vanadium nitrate ; The hafnium source is hafnium tetranitrate; the copper salt is a mixture of copper nitrate and copper sulfate in a mass ratio of 2:3; the chromium source is chromium nitrate; the boron source is sodium borate; the mass ratio of the aluminum source, manganese source, molybdenum source, vanadium source, hafnium source, copper source, chromium source, tantalum source, boron source, citric acid and water is 1:0.18:0.05:0.075:0.025:0.13:0.23:0.01:0.001:0.5:11; the roasting is carried out in two steps, the first step is to pre-sinter at a constant temperature of 540°C in a muffle furnace for 2.5 hours, and the second step is to roast at 880°C in a muffle furnace for 8.5 hours.

[0067] The other nanomaterials are a mixture of nano-zirconium boride, nano-niobium boride, nano-titanium nitride, and nano-silicon nitride in a mass ratio of 1:1.1:1.8:0.8; the particle size of the other nanomaterials is 70nm; the dispersant is a mixture of soybean lecithin, polyethylene glycol 200, and polyethylene glycol 400 in a mass ratio of 1:2:3; the cellulose nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.; the initiator is azobisisobutyronitrile.

[0068] A method for preparing the ceramic splitting knife material comprises the following steps:

[0069] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0070] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0071] Step S3: sintering the green body to obtain a ceramic splitting knife material.

[0072] The drying in step S2 is carried out under vacuum, the drying time is 21 hours, and the drying temperature is 88°C; the screening in step S2 is through a 250-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 510°C, and the debinding time is 4.5 hours.

[0073] The sintering conditions in step S3 are: heating rate 5°C / min, sintering temperature 1630°C, and holding time 9h.

[0074] Embodiment 5, a ceramic splitting knife material, comprising the following components in parts by weight: 80 parts of base ceramic, 25 parts of multi-element alloy oxide, 8 parts of binder, 10 parts of other nanomaterials, 4 parts of dispersant, and 1.2 parts of stearic acid; the multi-element alloy oxide is Mn-Mo-V-Hf-Cu-Cr-Ta-Al-BO; the binder comprises the following raw materials in parts by weight: 8 parts of cellulose nanocrystals, 5 parts of sodium silicate, 3 parts of 2,4,6-trivinylcycloboroxine, 3 parts of N-trihydroxymethylmethylacrylamide, 2 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 3 parts of vinyltrimethoxysilane, and 0.1 parts of initiator.

[0075] The matrix ceramic is a mixture of aluminum oxide powder, rare earth oxide powder and zirconium oxide powder in a mass ratio of 70:12:20; the rare earth oxide powder is a mixture of scandium oxide powder, yttrium oxide powder and cerium oxide powder in a mass ratio of 0.2:1.2:1; the particle size of the matrix ceramic is 1500 mesh.

[0076] The preparation method of the multi-element alloy oxide comprises the following steps: adding an aluminum source, a manganese source, a molybdenum source, a vanadium source, a hafnium source, a copper source, a chromium source, a tantalum source, a boron source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out and grinding it, passing it through a 500-mesh sieve to obtain the multi-element alloy oxide; the aluminum source is aluminum nitrate; the manganese source is manganese nitrate; the molybdenum source is molybdenum nitrate; the vanadium source is vanadium nitrate; the hafnium source is hafnium tetranitrate; the copper salt is copper sulfate; the chromium source is chromium nitrate; the boron source is sodium borate; the mass ratio of the aluminum source, manganese source, molybdenum source, vanadium source, hafnium source, copper source, chromium source, tantalum source, boron source, citric acid and water is 1:0.2:0.05:0.08:0.03:0.15:0.25:0.01:0.001:0.5:12; the roasting is carried out in two steps, the first step is to pre-fire at a constant temperature of 550°C in a muffle furnace for 3h, and the second step is to roast at 900°C in a muffle furnace for 9h.

[0077] The other nanomaterials are a mixture of nano-zirconium boride, nano-niobium boride, nano-titanium nitride and nano-silicon nitride in a mass ratio of 1:1.2:2:0.8; the particle size of the other nanomaterials is 80nm; the dispersant is soybean lecithin; the cellulose nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.; the initiator is azobisisobutyronitrile.

[0078] A method for preparing the ceramic splitting knife material comprises the following steps:

[0079] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0080] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;

[0081] Step S3: sintering the green body to obtain a ceramic splitting knife material.

[0082] The drying in step S2 is carried out under vacuum, the drying time is 22 hours, and the drying temperature is 90°C; the screening in step S2 is through a 300-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 520°C, and the debinding time is 5 hours.

[0083] The sintering conditions in step S3 are: heating rate 6°C / min, sintering temperature 1650°C, and holding time 10h.

[0084] Comparative Example 1, a ceramic splitting tool material and a preparation method thereof, is substantially the same as Example 1, except that nano-niobium boride, hafnium source and 2,4,6-trivinyl boroxine are not added.

[0085] Comparative Example 2, a ceramic splitting knife material and a preparation method thereof, is basically the same as Example 1, except that no tantalum source, nano-titanium nitride and cellulose nanocrystals are added.

[0086] In order to further illustrate the beneficial technical effects of the ceramic splitting knife materials involved in each embodiment of the present invention, relevant performance tests were conducted on the ceramic splitting knife materials involved in Examples 1-5 and Comparative Examples 1-2; the test methods are as follows:

[0087] (1) Bending strength: 20 ceramic splitting knife samples were taken from each case and the bending strength of the samples was tested using a universal material tester according to the three-point bending method. The test results were averaged.

[0088] (2) Hardness: Two ceramic splitting knife samples were taken from each case. After polishing, the hardness of the samples was tested using a Vickers hardness tester, and the test results were averaged. The hardness is the Vickers hardness measured with a load of 1 kg.

[0089] (3) Apparent porosity: Tested in accordance with GB / T 25995-2010.

[0090] (4) Fracture toughness: Tested according to the three-point bending test in accordance with GB / T 23806-2009.

[0091]

[0092] As can be seen from Table 1, the ceramic splitting knife materials involved in the embodiments of the present invention have better mechanical strength, hardness and fracture toughness, and lower apparent porosity than the comparative products. The combined use of nano-niobium boride, hafnium source, 2,4,6-trivinyl cycloboroxine, tantalum source, nano-titanium nitride and cellulose nanocrystals is beneficial to improving the above properties.

[0093] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A ceramic splitting knife material, characterized in that: The invention comprises the following components in parts by weight: 60-80 parts of base ceramic, 15-25 parts of multi-element alloy oxide, 5-8 parts of binder, 5-10 parts of other nano-materials, 2-4 parts of dispersant, and 0.8-1.2 parts of stearic acid; the multi-element alloy oxide is Mn-Mo-V-Hf-Cu-Cr-Ta-Al-BO; the binder comprises the following raw materials in parts by weight: 6-8 parts of cellulose nanocrystals, 3-5 parts of sodium silicate, 1-3 parts of 2,4,6-trivinyl cycloboroxane, 1-3 parts of N-trihydroxymethyl methacrylamide, 1-2 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 1-3 parts of vinyl trimethoxysilane, and 0.04-0.1 parts of initiator; The matrix ceramic is a mixture of aluminum oxide powder, rare earth oxide powder and zirconium oxide powder in a mass ratio of (50-70):(8-12):(10-20); the rare earth oxide powder is a mixture of scandium oxide powder, yttrium oxide powder and cerium oxide powder in a mass ratio of 0.2:(0.8-1.2):1; the particle size of the matrix ceramic is 1000-1500 mesh; The preparation method of the multi-element alloy oxide comprises the following steps: adding an aluminum source, a manganese source, a molybdenum source, a vanadium source, a hafnium source, a copper source, a chromium source, a tantalum source, a boron source and citric acid to water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out and grinding it, passing it through a 300-500 mesh sieve to obtain the multi-element alloy oxide; the quality of the aluminum source, manganese source, molybdenum source, vanadium source, hafnium source, copper source, chromium source, tantalum source, boron source, citric acid and water is The ratio is 1:(0.1-0.2):0.05:(0.05-0.08):(0.01-0.03):(0.08-0.15):(0.15-0.25):0.01:0.001:0.5:(8-12); the calcination is carried out in two steps, the first step is to pre-calculate at a constant temperature of 450-550°C in a muffle furnace for 1-3h, and the second step is to calcine at 800-900°C in a muffle furnace for 6-9h; The other nanomaterials are a mixture of nano zirconium boride, nano niobium boride, nano titanium nitride and nano silicon nitride in a mass ratio of 1:(0.8-1.2):(1-2):0.8; the particle size of the other nanomaterials is 10-80nm.

2. The ceramic splitting knife material according to claim 1, characterized in that: The aluminum source is at least one of aluminum nitrate and aluminum chloride; the manganese source is at least one of manganese nitrate and manganese chloride; the molybdenum source is at least one of molybdenum nitrate and molybdenum chloride; the vanadium source is vanadium nitrate; the hafnium source is hafnium tetranitrate; the copper source is at least one of copper nitrate and copper sulfate; the chromium source is chromium nitrate; and the boron source is sodium borate.

3. The ceramic splitting knife material according to claim 1, characterized in that: The dispersant is at least one of soybean lecithin, polyethylene glycol 200 and polyethylene glycol 400; the length of the cellulose nanocrystal is 100-500nm and the diameter is 20-100nm; and the initiator is azobisisobutyronitrile.

4. A method for preparing the ceramic splitting knife material according to any one of claims 1 to 3, characterized in that: The steps include: Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder; Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body; Step S3: sintering the green body to obtain a ceramic splitting knife material.

5. The method for preparing the ceramic splitting knife material according to claim 4, characterized in that: The drying in step S2 is carried out under vacuum, the drying time is 18-22 hours, and the drying temperature is 78-90°C; the screening in step S2 is through a 100-300 mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 450-520°C, and the debinding time is 3-5 hours; the sintering treatment conditions in step S3 are: heating rate 2-6°C / min, sintering temperature 1450-1650°C, and insulation time 5-10 hours.

Citation Information

Patent Citations

  • Alumina ceramic splitting knife based on photocuring and manufacturing method thereof

    CN116199501B

  • Ceramic material with amorphous / nanocrystalline structure and method of producing the same

    CN101508574A

  • Aluminium oxide, titanium carbide and silicon nitride composite reinforced zirconium boride-based multi-element nano-composite ceramic die

    CN104163630A

  • Cellulose nanocrystalline-modified ceramic blank and preparation method thereof

    CN106495671A

  • Ceramic chopper material and preparation method thereof

    CN106995308A